Que bom te ver viva: vozes femininas reivindicando uma outra história - Kátia da Costa Bezerra (Estudos de Literatura Brasileira Contemporânea)
The right to determine the meaning of the military dictatorship in Brazil has been a constant dispute between members of the militant left and the military regime. The language used by the two groups constantly revolves around the mythic images of “heroes”, “victims”, “for the good of the people”. This essay focuses on Que bom te ver viva, by Lúcia Murat, who brings a new perspective to this debate. Taking as a point of departure the testimony of eight ex-political prisoners, the film attempts to answer the question: How did we survive?” The essay discusses how the movie builds frames of memory that go beyond those taken as representative.